Microencapsulation technology for lipase added infant formula to improve gastrointestinal digestion: a review - Sari, Ratna Nurmalita (UNIVERSITAS MUHAMMADIYAH MATARAM, 2024)
Lipase role in milk lipid digestion is crucial since fat is the common source of infant nutrition. Human milk as the golden standard of infant nutrition contains bile salt-stimulated lipase which plays a significant role in gaining baby’s weight. In achieving the goal of infant formula to mimic human milk, researchers are concerned to add lipase in infant formula called LAIF (lipase-added infant formula). Since lipase is heat labile, microencapsulation is needed as an approach to stabilize lipase by adding in infant formula. This article reviews the possibility of micro-encapsulation for optimizing the lipase addition. Alginate beads encapsulate product from algae which can be used since it is usually used in commercial powder infant formula. Milk proteins also an option since the proteins contain high nutritional values and are categorized as safe materials. In the legumes group, pea protein could be the prospective option since the material has good solubility in water, stability in high temperatures, and good foaming capacity. Microencapsulation technology makes it possible to make longer shef life and improving stability of lipase in infant formula.